유아의 정서지능과 또래유능성에 따른 행복감의 차이 - 하선아; Seon Ah Ha; 진미경; Mi Kyoung Jin (한국놀이치료학회지(놀이치료연구), 2014)
본 연구는 유아의 정서지능과 또래유능성에 따른 행복감의 차이를 검증하고자 하였다. 이를 위해 만 4, 5세 유아 355명을 대상으로 정서지능 체크리스트(만 4-5세용), 유아용 또래유능성 척도, 유아용 행복감 척도를 사용하여 그 차이를 규명하였다. 본 연구의 결과를 요약하면 다음과 같다. 첫째, 유아의 정서지능에 따른 행복감의 차이를 규명하고자 t-test를 실시한 결과, 유아의 정서지능에 따라 행복감의 총점 및 하위요인에서 모두 유의한 차이가 있는 것으로 나타났다. 즉, 정서지능이 높은 집단이 낮은 집단에 비해 행복감이 높았다. 둘째, 유아의 또래유능성에 따른 행복감의 차이를 규명하고자 t-test를 실시한 결과, 유아의 또래유능성에 따라 행복감의 총점 및 하위요인에서 모두 유의한 차이가 있는 것으로 나타났다. 즉, 또래유능성이 높은 집단이 낮은 집단에 비해 행복감이 높았다. 셋째, 정서지능과 또래유능성이 행복감에 미치는 상호작용 효과를 규명하기 위해 이원변량분석(two-way ANOVA)을 실시한 결과, 행복감의 총점 및 하위요인 모두에서 유아의 정서지능과 또래유능성의 상호작용 효과가 유의미하게 나타났다. The purpose of this study was to verify the differences in children`s happiness, according to the levels of the children`s emotional intelligence and peer competence. The subjects comprised 355 children between four and five years of age. The children were assessed by means of the Emotional Intelligence Checklist, Peer Competence Scale for child, and Happiness Scale for Children. The results were as follows: First, as a result of t-tests for verifying differences in happiness according to children`s emotional intelligence, the group with high emotional intelligence showed a higher happiness levels than the group with low emotional intelligence. Second, as a result of t-tests for verifying the difference in happiness according to children`s peer competence, the group with a high peer competence showed a higher happiness level than the group with low peer competence. Third, as a result of two-way ANOVA used to verify the interactional effect of children`s emotional intelligence and peer competence on their happiness levels, it was revealed that the interaction effects of children`s emotional intelligence and peer competence were significant in both the total score and sub-factors of happiness.